THE IMPLEMENTATION OF NUISANCE PERMIT AND CONTROL POLICIES TO ACHIEVE EXCELLENT SERVICE AT THE BANDUNG CITY INTEGRATED SERVICE AND LICENSING AGENCY - Dea Melati; Elen Sari (Journal of Public Administration, 2023)
Excellent service is one of the crucial issues in the implementation of regional autonomy in Indonesia. So far, public services still have a bad image in the eyes of the public. Service is considered so bureaucratic that it creates negative impressions and perceptions about bureaucracy. The notion that bureaucracy is irrational, wasteful, unproductive and trapped in ceremonial activities is actually more common in society. Based on the problems described above, this study aims to determine the effect of the implementation of the disturbance permit policy and control on the excellent service of the City of Bandung. The research method used is explanatory survey method. The variables of this study consist of the independent variables namely Policy Implementation and Control, while the dependent variable is Excellent Service. The data was obtained through employee and community respondents who took care of disturbance permits at the Bandung City Integrated Licensing Service Agency. Respondents were determined as many as 87 through the Likert Scale questionnaire questionnaire instrument. The results of data collection will be tested for validity and reliability using moment product correlation techniques and Alpha-Cronbach. The results of the study stated that there was a significant influence between variables. The results of the data prove that policy implementation and control of excellent service at the Bandung City Integrated Licensing Service Agency have a significant influence.